1996
DOI: 10.1073/pnas.93.25.14940
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of normal and mutant human presenilin function in  Caenorhabditis elegans

Abstract: We provide evidence that normal human presenilins can substitute for Caenorhabditis elegans SEL-12 protein in functional assays in vivo. In addition, six familial Alzheimer disease-linked mutant human presenilins were tested and found to have reduced ability to rescue the sel-12 mutant phenotype, suggesting that they have lower than normal presenilin activity. A human presenilin 1 deletion variant that fails to be proteolytically processed and a mutant SEL-12 protein that lacks the C terminus display considera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

19
248
4

Year Published

1997
1997
2001
2001

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 358 publications
(271 citation statements)
references
References 27 publications
19
248
4
Order By: Relevance
“…Previous studies have demonstrated that the egg-laying defects in C. elegans, lacking the PS1 homologue sel-12, can be rescued by ⌬E9 huPS1 (5). Moreover, we demonstrate here that ⌬E9 huPS1 can be stabilized without cleavage.…”
Section: Discussionsupporting
confidence: 64%
See 3 more Smart Citations
“…Previous studies have demonstrated that the egg-laying defects in C. elegans, lacking the PS1 homologue sel-12, can be rescued by ⌬E9 huPS1 (5). Moreover, we demonstrate here that ⌬E9 huPS1 can be stabilized without cleavage.…”
Section: Discussionsupporting
confidence: 64%
“…In parallel with increased mRNA expression after butyrate, immunoblots with PS1Loop antiserum, which is specific for epitopes in the loop domain of PS1 (9), revealed robust increases in the steady-state levels of wild-type and mutant fulllength huPS1 and in the PS1 17 kDa CTF (Fig. 1, B, lanes 2,3,5,6,8, and 9; C, lanes 2, 3, 5, 6, 8, and 9). Butyrate treatment of untransfected cells did not change the levels of full-length endogenous PS1 polypeptides or the levels of endogenous NTFs and CTFs (data not shown).…”
Section: Inducible Expression Of Wild-type and A246ementioning
confidence: 93%
See 2 more Smart Citations
“…Furthermore, the membrane topology of SEL-12 and PS1 appears to be similar (8)(9)(10). In addition to the functional and structural similarities, expression studies indicate that SEL-12 and human presenilins are expressed throughout development in many different cell types (3,4,7).…”
mentioning
confidence: 94%